Oligotyping and metagenomics reveal distinct Candidatus Accumulibacter communities in side-stream versus conventional full-scale enhanced biological phosphorus removal (EBPR) systems. (1st November 2021) - Srinivasan, Varun N.; Li, Guangyu; Wang, Dongqi; Tooker, Nicholas B.; Dai, Zihan; Onnis-Hayden, Annalisa; Bott, Charles; Dombrowski, Paul; Schauer, Peter; Pinto, Ameet; Gu, April Z.
Highlights: Distinct Accumulibacter communities were identified in two different EBPR processes. Oligotyping can reveal microdiversity in Accumulibacter communities. Three new Accumulibacter MAGs were recovered from full-scale EBPR processes. Two of the MAGs belong to clades without any previous representative genomes. Abstract: Candidatus Accumulibacter phosphatis (CAP) and its clade-level micro-diversity has been associated with and implicated in functional differences in phosphorus removal performance in enhanced biological phosphorus removal (EBPR) systems. Side-stream EBPR (S2EBPR) is an emerging process that has been shown to present a suite of advantages over the conventional EBPR design, however, large knowledge gaps remain in terms of its underlying ecological mechanisms. Here, we compared and revealed the higher-resolution differences in microbial ecology of CAP between a full-scale side-stream EBPR configuration and a conventional A2O EBPR process that were operated in parallel and with the same influent feed. Even though the relative abundance of CAP, revealed by 16S rRNA gene amplicon sequencing, was similar in both treatment trains, a clade-level analysis, using combined 16S rRNA-gene based amplicon sequencing and oligotyping analysis and metagenomics analysis, revealed the distinct CAP microdiversity between the S2EBPR and A2O configurations that likely attributed to the improved performance in S2EBPR in comparison to conventional EBPR. Furthermore, genome-resolved metagenomics enabled extraction of three metagenome-assembled genomes (MAGs) belonging to CAP clades IIB (RCAB4-2), IIC (RC14) and II (RC18), from full-scale EBPR sludge for the first time, including a distinct Ca. Accumulibacter clade that is dominant and associated only with the S2EBPR configuration. The results also revealed the temporally increasing predominance of RC14, which belonged to Clade IIC, during the implementation of the S2EBPR configuration. Finally, we also show the existence of previously uncharacterized diversity of clades of CAP, namely the clades IIB and as yet unidentified clade of type II, in full-scale EBPR communities, highlighting the unknown diversity of CAP communities in full-scale EBPR systems. Graphical abstract: Image, graphical abstract